Early childhood students' perceptions of studying by distance learning for the Diploma of Teaching (ECE) - June Kean (Flexible Learning Association of New Zealand, 2012)
Traditionally, tertiary teacher education has been delivered in New Zealand through face-to-face teaching courses with students listening and taking notes while receiving instruction from a lecturer. Interaction between lecturer and students in a classroom setting has been considered a vital component in this process. Today, political and public interest in distance learning has increased in countries where students seeking access to tertiary teacher education are geographically widely dispersed. There has also been a noticeable change in the composition of the student population. No longer largely restricted to school leavers, there has been an increase in mature and employed applicants seeking access to tertiary teacher education programmes. At the same time distance education technologies have expanded very rapidly. Advances in information and computer technology have provided impetus to the growth in distance learning (DL), and have prompted the rapid growth in a new mode of delivery, online learning (OL). Distance learning instruction can be delivered in a manner as similar as possible to traditional face-to-face teaching. This can be achieved through a classroom with two-way audiovisual interaction. This is the basis of the Iowa model which provides distance learners with experiences that mirror traditional face-to-face teaching, via a normal classroom setting, and live, two-way audiovisual interaction. On the other hand, the Norwegian model combines negotiated distance teaching with local face-to-face teaching (Schlosser & Anderson, 1994). This model could be said to be reflected in the approach adopted by several New Zealand teacher education providers, whereby distance learning students who are considered to be self-motivated are supplied with printed course material by post, some form of teleconferencing, access to further relevant literature via a Website and use of the institution's library resources. Ongoing support for their studies is provided by phone/ email contact by distance. On-campus or regionally located face-to-face study weeks (contact courses) are provided on a regular basis to allow for peer/staff contact and interaction. This paper is structured as follows: Background information is provided on the tertiary institution in which the study was conducted. The major purpose of the study is outlined. TI1(' aspects of DL receptivity as contained in the questio1U1aire are indicated. A description of the sample follows. The results of till' survey are reported and then discussed in terms of recent literature. The limitations of the study are indicated. Issues and factors that have influenced the perceptions of students are analysed and future directions are considered in the delivery of this distance learning mode for early childhood teacher education.